The Long Sinuous Rille System in Northern Oceanus Procellarum and Its Relation to the Chang'e‐5 Returned Samples. Issue 11 (31st May 2021) - Qian, Yuqi; Xiao, Long; Head, James W.; Wilson, Lionel
Abstract: China's Chang'e‐5 (CE‐5) mission recently returned samples from a young intermediate‐Ti mare unit (Em4/P58, ∼1.5 Ga) in Northern Oceanus Procellarum. Rima Sharp, previously mapped as the longest lunar sinuous rille, is the most prominent volcanic feature associated with the landing region. Our analysis shows that Rima Sharp is not a single rille, but instead is composed of two separate rilles (Rima Sharp, originating from the North Vent, and Rima Mairan from the South Vent), meeting at ∼40.40°N, 48.38°W. Both vent have characteristics suggesting relatively low magma volatile contents. Rima Mairan and associated lavas (southeast of Em4/P58), embay and are slightly younger than Rima Sharp. Rille formation is largely influenced by pre‐existing topography (earlier mare surface, proto‐wrinkle ridges, highlands); rilles and deposits experienced post‐formation deformation (wrinkle ridges, mare subsidence). CE‐5 samples probably originate mainly from Rima Sharp's source vent, but may represent deposits from both rilles. Plain Language Summary: A major unanswered question in lunar science is the age and nature of the youngest lunar lava flows, located in the northwest nearside of the Moon but unsampled by Apollo or Luna missions. How long did internal activity and eruption of lavas continue on the Moon? Also very poorly known is the impact flux in the last third of Solar System history. Craters counted on a geologically young lava flow radiometrically dated in the laboratory would answer this question. China's Chang'e‐5 (CE‐5) mission recently returned samples from just such a young mare unit. But how was this unit emplaced and how does this help us understand the nature of the lava source regions? Rima Sharp, previously thought to be the longest lunar sinuous rille, crosses the young unit. We find that Rima Sharp is actually formed by two rilles, the 320 km‐long Rima Sharp and the 150 km‐long Rima Mairan, that meet in the middle of the unit. Detailed analysis shows that Rima Sharp was first, forming most of the young basalt unit, followed closely by Rima Mairan, embaying Rima Sharp. Samples returned by CE‐5 are most likely to be from the Rima Sharp eruption. Key Points: The lunar sinuous rille Rima Sharp is associated with the mare unit sampled by Chang'e‐5, and may have emplaced the unit Rima Sharp is actually formed by two rilles, ∼320 km long Rima Sharp and ∼150 long km Rima Mairan, that meet in the middle of the unit Rima Sharp formed first, emplacing most of the lava forming the young basalt unit, followed closely by Rima Mairan, embaying Rima Sharp